Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/esp.4102
|View full text |Cite
|
Sign up to set email alerts
|

Solifluction meets vegetation: the role of biogeomorphic feedbacks for turf‐banked solifluction lobe development

Abstract: Vegetation is an important factor influencing solifluction processes, while at the same time, solifluction processes and landforms influence species composition, fine‐scale distribution and corresponding ecosystem functioning. However, how feedbacks between plants and solifluction processes influence the development of turf‐banked solifluction lobes (TBLs) and their geomorphic and vegetation patterns is still poorly understood. We addressed this knowledge gap in a detailed biogeomorphic investigation in the Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 114 publications
1
59
0
Order By: Relevance
“…Furthermore, in addition to water, nutrients availability and the microclimate, plant colonization also depends on surface stability (Baroni et al, 2007;Gentili et al, 2010;Baroni et al, 2013). Such a two-way linkage was confirmed by other authors studying the interactions between subalpine alluvial fans and floristic diversity (Lane et al, 2016) and between sediment reworking on a lateral Little Ice Age (LIA) moraine and bioengineering species (Eichel et al, 2016;Eichel et al, 2017).…”
Section: Introductionmentioning
confidence: 61%
“…Furthermore, in addition to water, nutrients availability and the microclimate, plant colonization also depends on surface stability (Baroni et al, 2007;Gentili et al, 2010;Baroni et al, 2013). Such a two-way linkage was confirmed by other authors studying the interactions between subalpine alluvial fans and floristic diversity (Lane et al, 2016) and between sediment reworking on a lateral Little Ice Age (LIA) moraine and bioengineering species (Eichel et al, 2016;Eichel et al, 2017).…”
Section: Introductionmentioning
confidence: 61%
“…Considerably less research addressed the questions (a) what happens when gullying ceases and (b) how lateral moraines finally become stable. Eichel, Corenblit, and Dikau () and Eichel et al () suggested that colonization by so‐called ecosystem engineer species can play an important role for the change from dominant slopewash to solifluction processes on lateral moraine slopes. Ecosystem engineers are species that change their physical environment, for example, material and surface properties, thereby influence occurring geomorphic processes and create habitats for other species (Jones, Lawton, & Shachack, ; Eichel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two abiotic factors, namely water availability and disturbance 64 potential, have recently gained more attention as they represent dynamic physical factors within 65 glacial forefields that create strong stress gradients, and are therefore important in driving 66 ecosystem succession (Eichel et al, 2013;Gurnell et al, 1999;Levy et al, 2015;Mercier et al, 67 2009; Stawska, 2017). Our understanding of biotic factors is also evolving rapidly with new 68 research investigating the succession of microbial and vegetation communities, and the important 69 role they can play as ecosystem engineers (Eichel et al, 2016(Eichel et al, , 2017Frey et al, 2013;Raab, 70 2012; Schulz et al, 2013;Viles, 2012). With a better understanding of the interactions between 71 these factors, biogeomorphic feedbacks are starting to be considered an important part of 72 ecosystem succession; however, these feedbacks are not explicitly addressed in Matthews (1992) finally an ecological phase (biotic factors dominant) (Corenblit et al, 2007).…”
mentioning
confidence: 99%
“…Based on the impact that vegetation has been shown to have on 475 disturbance mechanisms on moraines and solifluction lobes within high altitude paraglacial 476 systems (e.g. Eichel et al, 2017Eichel et al, , 2016Eichel et al, , 2013, it seems reasonable that the same stabilizing 477 mechanisms could also influence surface water flow in glacial meltwater channels. Further 478 research is needed to elucidate the relationship between vegetation and water flow, and the 479 potential for biogeomorphic feedbacks in paraglacial environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation